Student Participation in Physical Activity Recess Programs in Secondary Schools. (2nd October 2022) - Drijvers, Hannelore; Seghers, Jan; van der Mars, Hans; Iserbyt, Peter
ABSTRACT: School recess, a component within the Comprehensive School Physical Activity Program (CSPAP), provides an opportunity to increase children's physical activity (PA). Although various studies have described PA interventions during recess, little is known about the effect of age, gender, and gross motor skill level on participation in such programs. The aim of this study was to investigate how student participation varied as a function of age, gender, and motor skill level. A cross-sectional survey was conducted in a sample of 1910 students (1010 girls, 900 boys) from first (13–14 years), second (15–16 years), and third (17–18 years) cycle from 15 secondary schools. Physical education teachers categorized students as lower-, average-, or higher-skilled based on previous skill assessments. Of all contacted schools, 80% offered at least one PA recess program during the year, of which 58% were team physical activities and 42% were individual activities. Overall, 62% of students did not participate, 25% participated in team physical activities, and 13% in individual physical activities. Students' participation was significantly different as a function of age: 44.7% participated in first, 37.8% in second, and 29.9% in third cycle ( p < .001). Boys participated significantly more in PA recess programs than girls (55.5% vs. 24.9%) ( p < .001). Lower skilled students (19.9%) participated significantly less than average skilled (28.6%) and higher skilled students (41.4%) ( p < .001). It can be concluded that PA recess programs should be designed to attract a larger proportion of girls and lower skilled students, possibly by connecting these programs with the content of physical education.